2018
DOI: 10.1038/s41584-018-0065-x
|View full text |Cite|
|
Sign up to set email alerts
|

B cell therapy in ANCA-associated vasculitis: current and emerging treatment options

Abstract: Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is an organ-threatening and life-threatening multi-system autoimmune disease in which B cell-derived ANCAs cause neutrophil activation and endothelial damage, strongly implicating these autoantibodies in the pathogenesis of AAV. B cell depletion with rituximab combined with glucocorticoids is associated with a reduction in ANCA concentrations and with clinical remission in the majority of patients with AAV. However, the safety profile of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 121 publications
0
49
0
3
Order By: Relevance
“…За последние 10 лет было проведено несколько рандомизированных контролируемых исследований (РКИ; табл. 3) и открытых клинических исследований, свидетельствующих об эффективности РТМ в качестве компонента индукционной и/или поддерживающей терапии у пациентов с недостаточной эффективностью ГК и иммуносупрессивных препаратов (в первую очередь ЦФ) у пациентов с АНЦА-СВ [47].…”
Section: системные васкулитыunclassified
“…За последние 10 лет было проведено несколько рандомизированных контролируемых исследований (РКИ; табл. 3) и открытых клинических исследований, свидетельствующих об эффективности РТМ в качестве компонента индукционной и/или поддерживающей терапии у пациентов с недостаточной эффективностью ГК и иммуносупрессивных препаратов (в первую очередь ЦФ) у пациентов с АНЦА-СВ [47].…”
Section: системные васкулитыunclassified
“…However, long-term glucocorticoid treatment is often needed to maintain remission and prevent disease flares. Therefore, to avoid excessive exposure to glucocorticoids and, more importantly, to promote a long-lasting remission of the disease, there is a need for alternative effective treatment options [6].…”
Section: Anca-associated Vasculitismentioning
confidence: 99%
“…Indeed, B cell depletion with the anti-CD20 antibody rituximab has demonstrated to provide beneficial effects in several autoimmune disorders [2][3][4][5]. Rituximab is currently approved for ANCA-associated vasculitis, based on the results of two randomized controlled trials (RCTs) that showed its efficacy in inducing disease remission [6]. Conversely, although commonly used off-label, in systemic lupus erythematosus (SLE) and systemic sclerosis (SSc), the use of rituximab is not supported by solid evidence deriving from RCTs, but mostly derived from observational studies [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Заболевания Показания РА [14,15] АНЦА-СВ [16,17] СКВ [18][19][20] СШ [21,22] ИВМ [23,24] Возможно назначение в качестве первого ГИБП у высоко-серопозитивных по АЦЦП и IgM РФ Другие показания для назначения в качестве первого ГИБП ционной и/или поддерживающей терапии у пациентов с АНЦА-СВ и недостаточной эффективностью ГК и иммуносупрессивных препаратов, в первую очередь циклофосфамида (ЦФ) [31,32]. В многоцентровое рандомизированное контролируемое исследование RAVE были включены пациенты с рецидивирующим или впервые диагностированным АНЦА-СВ [33].…”
Section: таблица 2 показания к применению ритуксимаба при иммуновоспunclassified